STUDY OF COMMUNITY PARTICIPATION IN THE ESTABLISHMENT OF QANUN OF VILLAGE LAW IN ACEH BESAR DISTRICT - Sulaiman Sulaiman; Hasbi Ali; Susiana Susiana (Geuthèë Institute, Aceh, 2022)
This article wants to analyze community participation in the process of drafting qanun of village in Aceh Besar District. Community participation is very important in drafting qanun because good law is based on efforts to ensure that the principle of participation runs well. This research was conducted by examining legal materials related to the formation of good law, especially qanun. Based on these provisions, then the process of community involvement in each stage of the formation of the qanun of village is explored. This study finds that public participation in the formation of qanun of village is still limited. This limitation is caused by a number of factors, including socialization that has not been carried out optimally by the village leadership. In addition, there is the problem of the availability of a very small budget for the process of forming the qanun. It is recommended to the Aceh Besar District Government to prepare guidelines for the drafting of the village qanun, in which the public involvement process is well regulated.